2021
DOI: 10.3389/fphys.2021.632883
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic Analysis of the Heart Rate Variability During the Plateau Phase Following Maximal Sprint Exercise

Abstract: Cardiac autonomic control is commonly assessed via the analysis of fluctuations of the temporal distance between two consecutive R-waves (RR). Cardiac regulation assessment following high intensity physical exercise is difficult due to RR non-stationarities. The very short epoch following maximal sprint exercise when RR remains close to its lowest value, i.e., the PLATEAU, provides the opportunity to evaluate cardiac regulation from stationary RR sequences. The aim of the study is to evaluate cardiac autonomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
(109 reference statements)
0
14
0
Order By: Relevance
“…Very recently (2021) Storniolo et al (2021) analyzed results of symbolic markers pre, post, and during a plateau phase—very short epoch (22 ± 8 cardiac beats, corresponding to 9 ± 3 s.) following maximal sprint exercise—in physically active subjects. Authors observed increased 2UV% and unvaried 0V% during plateau compared to pre sequences, suggesting a remarkable vagal modulation and persistency of the sympathetic control, respectively; 0V% significantly decreased and 2UV% was significantly higher in post compared to pre sequences, suggesting a less active sympathetic and more active vagal control in post than pre sequences, respectively ( Storniolo et al, 2021 ). Authors underlined that such conclusions cannot be achieved from the LF/HF ratio parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently (2021) Storniolo et al (2021) analyzed results of symbolic markers pre, post, and during a plateau phase—very short epoch (22 ± 8 cardiac beats, corresponding to 9 ± 3 s.) following maximal sprint exercise—in physically active subjects. Authors observed increased 2UV% and unvaried 0V% during plateau compared to pre sequences, suggesting a remarkable vagal modulation and persistency of the sympathetic control, respectively; 0V% significantly decreased and 2UV% was significantly higher in post compared to pre sequences, suggesting a less active sympathetic and more active vagal control in post than pre sequences, respectively ( Storniolo et al, 2021 ). Authors underlined that such conclusions cannot be achieved from the LF/HF ratio parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Authors underlined that such conclusions cannot be achieved from the LF/HF ratio parameter. Moreover, they suggested that future studies should evaluate the eventual association of the symbolic measures with the athlete’s performance ( Storniolo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation is a result of multiple mechanisms [1][2][3][4][5][6][7]. There is a change in the strength of the triceps brachii after training without correlation to fatigue rate (FR) or decrease in strength (DS).…”
Section: Adaptation Mechanisms Are Associated With a Plateau In Muscl...mentioning
confidence: 99%
“…Variability is inherent to the normal function of body systems and can be identified at the genomic and the cellular levels or based on the function of whole organs [1,63]. It is described as the body's response while attempting to reach an optimal steady-state or part of its compensatory adaptation to the continuous internal and external triggers.…”
Section: Variability In Biological Systems Characterizes the Typical ...mentioning
confidence: 99%
“…Withal, it is well known that in the post-transplant period, heart failure persists in a number of patients, despite the good contractility of the donor heart, thus significantly limiting their rehabilitation [9]. Apparently, vagal innervation of the heart is important in ensuring the physical working capacity, which starts to increase in the early recovery period after physical training [10], and is a prognostic marker in patients with pathology of the circulatory system [11]. Role of the parasympathetic nervous system in maintaining physical working capacitance remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%